The Trickster - Anderson, Laurie Halse (Vet volunteers, 2008)
When he and the other volunteers at Dr. Mac's veterinary clinic go to help out at Quinn's Stables, David makes several serious mistakes and must prove he can be trusted before Mr. Quinn will let him even be around the spirited horse that David wants to ride.